2004
DOI: 10.1111/j.1467-9450.2004.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of parental sensitivity towards pre‐school children born with very low birth weight

Abstract: The article introduces the Parental Sensitivity Assessment Scale (PSAS) and examines the influence of the PSAS score and other factors on the general cognitive level in pre-school children born with very low birth weight (VLBW). McCarthy general cognitive index (GCI) was obtained for 102 VLBW and 92 normal birth weight (NBW) control children in Denmark in the mid-1980s. The mean ages of the two groups were 52.4 vs. 53.1 months. Parental sensitivity was assessed using PSAS. There was no significant difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
10
0
3
Order By: Relevance
“…A recent study using a questionnaire on parental attitudes showed that a loving, supporting parental style was a positive predictor of both verbal and performance IQ in children born at term (Sommerfelt et al ., 2000). This finding is corroborated by a study using observation of parental behaviors towards children born very prematurely (Hoff, Munck & Greisen, 2004).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…A recent study using a questionnaire on parental attitudes showed that a loving, supporting parental style was a positive predictor of both verbal and performance IQ in children born at term (Sommerfelt et al ., 2000). This finding is corroborated by a study using observation of parental behaviors towards children born very prematurely (Hoff, Munck & Greisen, 2004).…”
Section: Introductionsupporting
confidence: 68%
“…The total score ranged from 2 to 11 with a higher score indicating a higher educational level. For further detail see Hoff et al (2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding could help explaining the results of a recent Danish register-based study showing that the vast majority of VPT individuals born in 1974–76 actually seem well integrated in society at age 27–29 years [25]. The increase in agreeableness appeared to be unrelated to the educational level of the parents, but maybe environmental factors such as increased parental sensitivity observed in a controlled study of VPT children at pre-school age [26] could explain our finding of higher scores on agreeableness. We speculate that early parental adjustment to their very preterm child may have long-term benefits in helping the child to develop an optimistic attitude and confidence in others that are positively associated with adjustment in adult life.…”
Section: Discussionmentioning
confidence: 62%